Redox Chemistry of 9,10-diacetoxy-1,4-methano-1,4-dihydroanthracene Derivatives - Kysely, Taylor N.; Lyons, Zoe A.; Wilson, Megan B.; Lewis, David E. (My University, 2017)
The epoxide (2) of the title compound (1) has been found to have unusual oral anticoagulant activity in rats: At day 4 of co-administration with warfarin, it is a potent antagonist of anticoagulation; at day 10 of co-administration, the compound is now a potent agonist of anticoagulation. We have determined that the active principle of the anticoagulation is not a simple conjugate of warfarin with the epoxide. Herein, the hydrolysis of the diacetates 1 and 2 under acid and base conditions, and the redox chemistry of the resulting naphthalenediol derivatives and their analogs in air will be discussed.
Color poster with text, charts, and images.
Keywords: Organic reaction mechanisms; Organic chemistry; Posters